How Investors Attitudes Shape Stock Market Participation in the Presence of Financial Self-Efficacy - Nadeem, Muhammad Asif; Qamar, Muhammad Ali Jibran; Nazir, Mian Sajid; Ahmad, Israr; Timoshin, Anton; Shehzad, Khurram (Frontiers in Psychology, 2020)
The purpose of this study is to investigate how investor’s money attitudes shape their stock market participation (SMP) decisions. This study followed the Theory of Planned Behavior (TPB) and a survey was conducted to collect the responses from active investors. Structural Equation Modeling (SEM) was used for the analysis of hypothesized relationships among the constructs and Confirmatory Factor Analysis (CFA) was conducted to check the interrelation of the variables and validity of the constructs. This research concluded that investor’s money attitudes are significant to affect their stock market participation decisions. Further, it was found that risk attitudes mediate the relationship between money attitudes and stock market participation. Moreover, financial knowledge and financial self-efficacy positively moderate the relationship between money attitudes and stock market participation. This research is one of the early attempts to study the money attitudes of investors and introduce financial self-efficacy as moderating construct between money attitudes and stock market participation. The sample size for this study was 250 respondents which can be increased, and the same relationships can be tested by using a large sample. Moreover, this study used money attitudes as predictors of stock market participation but many other variables like personal value can also be taken to investigate their influence on stock market participation.